2016
DOI: 10.1177/0886260516660298
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing the Myths About Intimate Partner Violence: A Critical Discourse Analysis of News Reporting in Hong Kong

Abstract: This article depicts the dominant discourses on intimate partner violence (IPV) in newspaper reports and discusses how the myths about IPV are perpetuated in news reporting in Hong Kong. The myths about IPV consist of a set of prevalent assumptions in society that adversely affect the help-seeking behavior of survivors and impede social change. It is sometimes assumed that the victims cause the abuse and are personally responsible for solving the problem. This study reveals how news reporting in Hong Kong perp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 31 publications
3
26
0
1
Order By: Relevance
“…In terms of the research done on domestic violence coverage, the present effort was consistent with the previous literature (Chan, 1997; Ferrand Bullock, 2007; Ferrand Bullock & Cubert, 2002; Gillespie et al, 2013; Leung, 2016; Richards et al, 2011; Taylor, 2009): Official authorities remained the main sources of information and domestic violence continued to be seen as an isolated crime, disconnected from the control and power issues in the relationship. In addition, the Hong Kong newspaper explained the events from the dominant ideology, as breaches of societal female roles, such as “fidelity,” “loyalty,” “obedience,” or “respect,” which served as precipitators for the attacks.…”
Section: Discussion and Limitationssupporting
confidence: 85%
See 2 more Smart Citations
“…In terms of the research done on domestic violence coverage, the present effort was consistent with the previous literature (Chan, 1997; Ferrand Bullock, 2007; Ferrand Bullock & Cubert, 2002; Gillespie et al, 2013; Leung, 2016; Richards et al, 2011; Taylor, 2009): Official authorities remained the main sources of information and domestic violence continued to be seen as an isolated crime, disconnected from the control and power issues in the relationship. In addition, the Hong Kong newspaper explained the events from the dominant ideology, as breaches of societal female roles, such as “fidelity,” “loyalty,” “obedience,” or “respect,” which served as precipitators for the attacks.…”
Section: Discussion and Limitationssupporting
confidence: 85%
“…In Chinese society, there is little analysis following media coverage of female violence (Chan, 1997;Gilmartin, 1990;Leung, 2016). This research, however, found similar patterns to those of the American and European studies: victims being blamed for their abuse, hot-tempered men, and stories that disregarded the hierarchy derived from gender.…”
Section: Framing and The Social Construction Of Domestic Violencesupporting
confidence: 59%
See 1 more Smart Citation
“…Más recientemente, se han extraído conclusiones similares en el ámbito de la violencia de género (Bosch y Ferrer 2002;2012;Bosch et al 2013;Leung 2019;Megías, Toro-García y Carretero-Dios 2018;Policastro y Payne 2013;Yamawaki et al 2012;Westbrook 2009). Uno de los trabajos más relevantes a nivel nacional fue el desarrollado por Bosch y Ferrer (2012), quienes propusieron una clasificación de los principales mitos sobre la violencia de género en cinco categorías, diferenciando entre los mitos sobre la marginalidad del fenómeno, los referidos a los maltratadores, los mitos sobre las mujeres maltratadas, aquellos que minimizan la importancia de la violencia de género y los mitos negacionistas.…”
Section: Antecedentes Teóricos Y Empíricosunclassified
“…From these studies, it becomes clear in the Asian context that questions have moved beyond a positivistic framework of assessing the nature and extent of media distortion. Scholars have examined the construction of “social panic” by the state and the media in Hong Kong (Ku, 2001); the stereotyping of intimate partner violence abusers and victim blaming in the Hong Kong press (Leung, 2016); police scandals and the myth of the “collapse of secure society” in Japan (Hamai and Ellis, 2008); “mediatized violence” and the framing of Korean protesting farmers (Leung, 2009); and protestors, corruption, and morality in China (Barbour and Jones, 2013; Hsu, 2001; Murphy, 2007). One common theme emerging from these studies is the media’s projection of “threats to the nation”.…”
Section: Contributions Of Media and Cultural Studiesmentioning
confidence: 99%